Correlation between use of simvastatin and lovastatin and female lung cancer risk: a nationwide case–control study. Issue 5 (25th November 2014) - Yang, T.‐Y.; Lin, W.‐M.; Lin, C.‐L.; Sung, F.‐C.; Kao, C.‐H.
Summary: Background: The objective of this study was to determine the association between statin use and female lung cancer in Taiwan. Methods: In this case–control study, we used information from the Taiwan National Health Institute Research Database on 17, 329 patients (cases) aged 20 years or older recently diagnosed with lung cancer between 2005 and 2010 and 17, 329 patients without lung cancer to assess the association between female lung cancer and statin use, even adjustment for its comorbidities. Results: After adjusting for age and associated risk factors, we determined that women who engaged in long‐term use of simvastatin at a defined daily dose (DDD) of over 150 have a reduced risk of lung cancer compared with those who did not use statins (odds ratio: 0.77, 95% confidence interval: 0.62–0.97) in women. However, lovastatin was not significantly associated with lung cancer in women. Among female patients with pre‐existing comorbidities of respiratory diseases such as chronic obstructive pulmonary disease, hypertension, stroke and pulmonary tuberculosis, statins reduced the risk of lung cancer. Conclusions: Simvastatin use at a DDD of more than 150 is correlated with an approximately 20% reduction in the risk of lung cancer in women.